BULLETIN VULCANOLOGIQUE - Raccichini, S. (2011)
Esta nota corresponde al BULLETIN VULCANOLOGIQUE de Journal of the International Association Of Volcanology and Chemistry of the Earths Interior, of the International Union of Geolosy and Geoghysicas. Editor: Dr. Esu Cugusi, Centro di Studio per la geologia técnica, CNR Instituto di Geologia Applicata, Via Budossiana, 18-00184 Roma, Italia.